2016
DOI: 10.21608/absb.2016.24336
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Allometry, Sexual Dimorphism and Age Structure in Sample of the Egyptian Wolf Canisanthuslupaster

Abstract: The study investigates the occurrence of age-related allometric changes in a number of cranial and dental measurements of the Egyptian wolf Canis anthus lupaster from different areas of Egypt.The age structure of a sample of 55 specimens of both sexes of C.a. lupaster was investigated using counting dentine layers on longitudinally sanded canine roots.The results showed that most of the wolves were between one and three years of age. The oldest individual was 11 years old. A set of isometric cranial and dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Few studies have reported SSD in African wolves. For Egyptian specimen of African wolves, male and female dimensions appeared to be different (Osborn and Helmy 1980;Younes and Fouad 2016). The skulls of males are relatively wider, and females tended to have a shorter snout (Younes and Fouad 2016).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Few studies have reported SSD in African wolves. For Egyptian specimen of African wolves, male and female dimensions appeared to be different (Osborn and Helmy 1980;Younes and Fouad 2016). The skulls of males are relatively wider, and females tended to have a shorter snout (Younes and Fouad 2016).…”
Section: Introductionmentioning
confidence: 88%
“…For Egyptian specimen of African wolves, male and female dimensions appeared to be different (Osborn and Helmy 1980;Younes and Fouad 2016). The skulls of males are relatively wider, and females tended to have a shorter snout (Younes and Fouad 2016). Van Valkenburgh and Wayne (1994) found SSD in the mediolateral dimension of the upper canine in both the golden jackal and the African wolf, where the average difference was 4% (in a range of 0-13%).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to 8 indices were calculated. The parameters measured were adopted from those reported previously [ 22 , 31 , 33 , 37 ]. Skull indices were calculated following the method reported by Andreis et al [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, canine morphometric measurements have been reported to be helpful tool for calculation of the total intraconal anesthetic volume [ 29 ] The phenotypic variation in the red fox skull results from natural selection while that of the domestic dog results from artificial selection or domestication [ 30 ]. Several studies have been done to investigate the morphometric measurements of skulls in several Canid species including the red fox, silver fox, corsac fox, golden jackals, Egyptian wolf, dog, lion, and cat [ 22 , 25 , 27 , 31 – 38 ]. These studies revealed that morphometric measurements of the skull are crucial for species identification.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies made by Özcan et al (2010), Karimi et al (2011), Dalga et al (2018), Popoola and Oseni (2018), Choudhary et al (2020), Gündemir et al, (2020a), Jashari et al (2022), different sheep skulls were studied and differences between breeds were revealed. Other morphometric studies are undertaken in the skull of different Canids to reveal their features and to use these data in specie identification or in comparative studies such as in dogs (Daskiran & Cedden, 2006; İlgün et al, 2022; Monfared, 2013; Onar, 1999; Onar et al, 2001), lions (Zuccarelli, 2003), cats (Saber et al, 2016) felines (Saber & Gummow, 2015), red foxes (Munkhzul et al, 2018; Onar et al, 2005), wolfs and jackals (Andersone & Ozolins, 2000; Janssens et al, 2019; Milencovic et al, 2010; Rezić et al, 2017; Srinivas & Jhala, 2021; Stoyanov, 2012; Younes & Fouad, 2016).…”
Section: Introductionmentioning
confidence: 99%